It's Not All about the Economy Stupid! Immigration and Subjective Well-Being in England. (October 2020) - Howley, Peter; Waqas, Muhammad; Moro, Mirko; Delaney, Liam; Heron, Tony
While much is known regarding the effects of immigration for objective outcomes, relatively little is known regarding the effects for perceived well-being. By exploiting spatial and temporal variation in the net-inflows of foreign-born individuals across local areas in England, we examine the relationship between immigration and natives' subjective well-being as captured by the General Health Questionnaire (GHQ). We find small negative effects overall but that an analysis of the main effects masks significant differences across subgroups, with relatively older individuals, those with below-average household incomes, the unemployed and finally those without any formal educational qualifications experiencing much more substantive well-being losses than others. These observed well-being differentials are congruent with voting patterns evident in the recent UK referendum on EU membership. We put forward perceived as opposed to actual labour market competition and social identity as two potential explanations for the negative well-being impacts of immigration for natives.